NLRP3 Inflammasome: A Promising Therapeutic Target for Drug-Induced Toxicity - Wei, Shanshan; Ma, Wanjun; Zhang, Bikui; Li, Wenqun (Frontiers in Cell and Developmental Biology, 2021)
Drug-induced toxicity is a serious problem during drug development and the clinical use of many marketed drugs, which impairs human organ functions, and the underlying mechanism is complicated. As a sensor of infections and external stimuli, NLRP3 inflammasome plays a key role in the pathological process of various diseases. In this review, we specifically focused on the role of NLRP3 inflammasome in drug-induced diverse organ toxicities, especially the hepatotoxicity, nephrotoxicity, and cardiotoxicity. NLRP3 inflammasome is involved in the initiation and deterioration of drug-induced toxicity through multiple signaling pathways. Therapeutic strategies via inhibiting NLRP3 inflammasome for drug-induced toxicity have made significant progress, especially the protective effects of the phytochemicals. Growing evidences collected in this review indicate that NLRP3 is a promising therapeutic target for drug-induced toxicity.